Synthesis and characterization of anodic titania nanotubes for supercapacitor application / Zulkarnain Endut - Zulkarnain, Endut (2013)
Over the past decade, titania nanotube materials have attracted increasing scientific and technological attention ranging from usage in the fields of biomedical applications to energy conversion. Titania nanotubes can be synthesized using a simple and low-cost self-organizing anodization method but is capable of producing highly ordered titania nanotube structures.This nanostructure grown directly on the conductive substrate can offer unique physical properties such as high specific surface area, lower electron recombination and excellent charge-transfer properties. Based on this motivation, this thesis attempts to synthesis, to apply, to investigate and to enhance this titania nanotubes as a binder-free supercapacitor electrode in which titanium foil can be used as a current collector while their nanotubular structure is used as charge storing and releasing area. The aim of this work is to study the structure, morphology, chemical composition and electrochemical capacitance performance by means of various characterization tools such as field emission scanning electron microscopy (FESEM), xray diffraction (XRD), x-ray photoelectron spectroscopy (XPS), cyclic voltammetry (CV), galvanostatic charge-discharge testing (CD), electrochemical impedance spectroscopy (EIS) and Mott-Schottky analysis. The thesis describes the mechanism of titania nanotube formation and growth during anodization of titanium in NH4F/ethylene glycol electrolyte at 45 V applied voltage that was investigated using FESEM. The initial stage of the anodization occurs with the formation of a compact oxide layer with nanoscale pits. With the increase of anodization time, the pits transform to larger and deeper pores due to the integration of the smaller and larger pores, finally creating selfordered titania nanotubes. The porous structure increases electrochemical capacitance from 18.3 μF cm-2 for 10-s anodization time to 49.9 μF cm-2 for 1800-s anodization time. The CV transforms from a near symmetry rectangular shape to x-axis symmetry